Developing Arabiyatuna Board Game for Engaging Students’ Knowledge Towards the Arabic Language & Culture - Abdul Rahim, Abdul Hadi; Hussin, Muhammad Hafizuddin; Awang Ali, Mohammad Amnan; Roslan, Muhammad Hanis; Hassan, Haslina; Abu Bakar, Radhwa (RSIS International, 2024)
This paper presents the development of the “Arabiyatuna” board game, a novel tool designed to enhance students’ understanding of the Arabic language and culture. The game employs engaging, interactive elements to facilitate learning, making it an effective educational resource. By immersing players in various aspects of Arabic language and culture, “Arabiyatuna” aims to foster a deeper appreciation and comprehension of the Arab world. The Arabiyatuna Board Game implements the ADDIE model as the primary model in developing the game. This model was implemented on the students of Kolej Universiti Islam Perlis (KUIPs). As a result, this innovative approach to language learning offers a unique blend of entertainment and education, promising a more engaging and enjoyable learning experience for the learners.